2016
DOI: 10.4306/pi.2016.13.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among Social Anxiety, Self-Esteem, Impulsivity, and Game Genre in Patients with Problematic Online Game Playing

Abstract: ObjectiveRecent studies of online game addiction have suggested that social interaction and impulsivity are critical factors for the etiology and progress of online game addiction. We hypothesized that the genre of the online game is associated with impulsivity and sociality in individuals with online game addictions.MethodsIn total, 212 patients with problematic online game playing were divided into four groups by game genre: 1) massive multiplayer online role playing game (MMORPG), 2) real-time strategy (RTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 40 publications
4
46
0
4
Order By: Relevance
“…Some studies have also shown that individuals characterized by a propensity to act impulsively use the game as an escape from reality to get away from painful emotions that derive from distorted beliefs relating to self, others and the surrounding world (38,39). In our study it emerged that somatization, depression and sleep disturbances are predictive in online gambling addiction behaviors, according to some literature data (33,40,41).…”
Section: Discussionsupporting
confidence: 60%
“…Some studies have also shown that individuals characterized by a propensity to act impulsively use the game as an escape from reality to get away from painful emotions that derive from distorted beliefs relating to self, others and the surrounding world (38,39). In our study it emerged that somatization, depression and sleep disturbances are predictive in online gambling addiction behaviors, according to some literature data (33,40,41).…”
Section: Discussionsupporting
confidence: 60%
“…Self-esteem, which is defined as one’s sense of self-worth or value and is one of the components of self-constructs along with self-efficacy, was negatively associated with internet addiction [ 62 , 63 ]. Additionally, several studies have suggested that self-esteem significantly predicts internet addiction [ 64 , 65 ], and a few studies have found that decreased self-esteem is related to online game use [ 66 ]. Working from the perspective that self-efficacy is a dimension of self-concept [ 67 ], Kim et al [ 68 ] found that individuals diagnosed with IGD were more likely than healthy controls to have a negative self-concept with regard to both their actual and their ideal selves according to neuroimaging analyses.…”
Section: Discussionmentioning
confidence: 99%
“…3) Clear data regarding comorbid diagnoses and personality ratings to ascertain to what extent IGD occurs independently of ADHD, depression, anxiety, etc. (50,62,63). 4) Longitudinal studies, which can help clarify which criteria are enduring and thus more clinically applicable (11,21,38).…”
Section: Discussionmentioning
confidence: 99%